A conceptual framework as basis for the development of a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide - Sumpi, Ndempavali; Amukugo, Hans Justus (International Journal of Health, 2016)
This paper focuses on the conceptualization the research findings and literature control with regard to the experiences of women who have dumped babies and / or committed infanticide. Eleven unstructured individual interviews were voice recorded and transcribed verbatim. The researcher used a systematic approach to analyse the transcripts and field notes using Tesch’s open qualitative data analysis method Based on the findings of the main themes of the study, four central concepts emerged from those themes; namely psychological factors, socioeconomic factors, the reintegration process, as well as a legal and ethical framework. Through consultation and member checking, it was concluded that an educational programme was suitable to prepare and support the women who had dumped babies and / or committed infanticide.The educational programme entailed the management and understanding of the psychosocial aspects, socioeconomic aspects, reintegration process, as well as the legal and ethical aspects of the women. These women are members of the society irrespective of the magnitude of the crime they had committed.The conceptual framework forms the basis of the development of the training programme for women who have dumped babies and / or committed infanticide. The description in this conceptual framework is in accordance with the reasoning map that is based on the survey list outline by Dickoff et al. (1968).